2015
DOI: 10.1353/jda.2015.0144
|View full text |Cite
|
Sign up to set email alerts
|

Stock market and tax revenue as determinants of economic growth: Panel data evidence from developing Asia

Abstract: Traditional growth literature advocated the role of fiscal policy in establishing economic growth (Mckinnon, 1973; Schumpeter, 1911; Shaw, 1973; Solow, 1956; Zagler and Durnecker, 2003), but it did not consider the role of the stock market and the financial intermediation as the potential determinants of growth. Among those few economic theories explaining the stock market and taxation as joint determinants of the economic growth are the Levine’s (1991) endogenous growth models (EGM), which suggests that econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In a study of 10 developing Asian nations, it was found that the stock market and the tax revenue influences economic growth. The study results also indicate that for market economic progress, governments of the developing nations ought to improve the channels between the securities market, taxation policy, and economic process by developing securities market liquidity and by characteristic growth-oriented tax reform methods (Colombage, Maslyuk, & Taha, 2015). In another study the results…”
Section: Determinants Of Stock Market Developmentmentioning
confidence: 78%
“…In a study of 10 developing Asian nations, it was found that the stock market and the tax revenue influences economic growth. The study results also indicate that for market economic progress, governments of the developing nations ought to improve the channels between the securities market, taxation policy, and economic process by developing securities market liquidity and by characteristic growth-oriented tax reform methods (Colombage, Maslyuk, & Taha, 2015). In another study the results…”
Section: Determinants Of Stock Market Developmentmentioning
confidence: 78%